1994
DOI: 10.1007/bf02383380
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical study on the tissue compartmentalization of phosphophoryn, osteopontin and bone sialoprotein (BSP) in rat incisor dentin

Abstract: Abstract:The tissue compartmentalization of phosphophoryn, osteopontin (OPN) and bone sialoprotein (BSP) in dentin was biochemically analyzed. The radicular portion of rat incisor was excised and sequentially extracted; i.e., proteins non-covalently bound to matrix such as soft tissues were solubilized with 4 M guanidinium chloride (G1), mineral-binding proteins were then extracted with 0.5 M EDTA (E), proteins noncovalently bound to the collagen matrix were extracted with 4 M guanidinium chloride (G2) after E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Osteocalcin, one of the most abundant noncollagenous proteins in bone, has been detected in both the gap zone and the overlap zone of collagen fibrils and appear as single spheres or pearl necklace–like strings ( 14 , 15 ). Guanidine and collagenase extraction studies demonstrated that matrix phosphoproteins bind to collagen via ion association or covalent bonding ( 16 ). Collagen secreted by fibroblasts does not mineralize in the presence of mineralization precursors except for areas with ectopic calcification ( 17 ); matrix phosphoproteins are also involved in ectopic mineralization of vascular tissues ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Osteocalcin, one of the most abundant noncollagenous proteins in bone, has been detected in both the gap zone and the overlap zone of collagen fibrils and appear as single spheres or pearl necklace–like strings ( 14 , 15 ). Guanidine and collagenase extraction studies demonstrated that matrix phosphoproteins bind to collagen via ion association or covalent bonding ( 16 ). Collagen secreted by fibroblasts does not mineralize in the presence of mineralization precursors except for areas with ectopic calcification ( 17 ); matrix phosphoproteins are also involved in ectopic mineralization of vascular tissues ( 18 ).…”
Section: Introductionmentioning
confidence: 99%